Coalescent assimilation across word-boundaries in American English and in Polish English - Kaźmierski, Kamil; Wojtkowiak, Ewelina; Baumann, Andreas (Research in Language, 2016)
Coalescent assimilation (CA), where alveolar obstruents /t, d, s, z/ in word-final position merge with word-initial /j/ to produce postalveolar /tʃ, dʒ, ʃ, ʒ/, is one of the most wellknown connected speech processes in English. Due to its commonness, CA has been discussed in numerous textbook descriptions of English pronunciation, and yet, upon comparing them it is difficult to get a clear picture of what factors make its application likely. This paper aims to investigate the application of CA in American English to see a) what factors increase the likelihood of its application for each of the four alveolar obstruents, and b) what is the allophonic realization of plosives /t, d/ if the CA does not apply. To do so, the Buckeye Corpus (Pitt et al. 2007) of spoken American English is analyzed quantitatively. As a second step, these results are compared with Polish English; statistics analogous to the ones listed above for American English are gathered for Polish English based on the PLEC corpus (Pęzik 2012). The last section focuses on what consequences for teaching based on a native speaker model the findings have. It is argued that a description of the phenomenon that reflects the behavior of speakers of American English more accurately than extant textbook accounts could be beneficial to the acquisition of these patterns.